Thymolipoma in a 13-year-old Korean girl - Su-Jin Park; Ji Young Baek; Junjeong Choi; Kyung Won Kim; Myung Joon Kim; Myung Hyun Sohn; Kyu-Earn Kim (Korean Pediatric Society, 2010)
Thymolipoma is a rare benign tumor of anterior mediastinum. Most patients are asymptomatic with incidental finding of the tumor during a diagnostic workup of other medical problems. We present a case of 13-year-old girl with anterior mediastinal thymolipoma, surgically removed after an incidental diagnosis.